Programmed cell senescence in skeleton during late puberty - Changjun Li (Nature Portfolio, 2017)
Mesenchymal stem cells are essential for bone development, but it is unclear if their activity is maintained after late puberty, when bone growth decelerates. The authors show that during late puberty in mice, these cells undergo senescence under the epigenetic control of Ezh2.